2013
DOI: 10.1002/smll.201302676
|View full text |Cite
|
Sign up to set email alerts
|

RNAi‐Microsponges Form through Self‐Assembly of the Organic and Inorganic Products of Transcription

Abstract: Inorganic nanostructures have been used extensively to package nucleic acids into forms useful for therapeutic applications. Here we report that the two products of transcription, RNA and inorganic pyrophosphate, can self-assemble to form composite microsponge structures composed of nanocrystalline magnesium pyrophosphate sheets (Mg2P2O7·3.5H2O) with RNA adsorbed to their surfaces. The microsponge particles contain high loadings of RNA (15–21 wt.%) that are protected from degradation and can be obtained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 41 publications
4
91
0
Order By: Relevance
“…It was previously shown that long ssRNA molecules generated by RCA can form composite nanoparticles consisting of nucleic acids and magnesium pyrophosphate. 30 To better understand the structure of our DNFs, we used energy dispersive X-ray spectroscopy to analyze their elemental composition (Figure 2g). Energy dispersive X-ray spectroscopy confirmed the presence of nitrogen, oxygen, magnesium and phosphorus, which reveals that the DNFs are composed of DNA and magnesium pyrophosphate.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
“…It was previously shown that long ssRNA molecules generated by RCA can form composite nanoparticles consisting of nucleic acids and magnesium pyrophosphate. 30 To better understand the structure of our DNFs, we used energy dispersive X-ray spectroscopy to analyze their elemental composition (Figure 2g). Energy dispersive X-ray spectroscopy confirmed the presence of nitrogen, oxygen, magnesium and phosphorus, which reveals that the DNFs are composed of DNA and magnesium pyrophosphate.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
“…Inter-and intramolecular hybridizations tend to fold these linear chains into particles with the size affected by factors such as the selection [4,7] and concentration [8] of the polymerases, the elongation time [9] and so on. The magnesium pyrophosphate generated during the synthesis process, as a side product of the polymerized nucleotides, was recently reported to be necessary for the structural integrity of the nucleic acid particles [7,10]. In the pioneering work demonstrated by Hammond and coworkers, RNA microparticles composed of concatenated siRNA (more than half a million repeats per particle) were developed for siRNA delivery [2].…”
Section: Rcr Product Self-assembled Micro-nanoparticlesmentioning
confidence: 99%
“…Our strategy for developing Multi‐RNAi‐MSs as a drug‐delivery platform involved an additional condensation step by electrostatic interactions and physical agitation 5, 6, 7. In this study, positively charged linear polyethylenimine (PEI) was chosen to achieve effective intracellular uptake and endosomal escape.…”
mentioning
confidence: 99%